The Impact of Human Capital, Technology, and Government Consumption on Economic Growth in Regencies and Cities in East Java Province from 2015 – 2024 - Nadifa Auni Mayra; Nurul Subkhania (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2026)
This research examines the impact of human capital, technology, and government consumption on economic growth across districts and cities in East Java Province between 2015 and 2024. Economic growth serves as an indicator of regional development success and community welfare (Todaro Smith, 2015). In this study, technology is proxied by the level of internet usage at the district and city levels. The research applies the framework of endogenous growth theory using regional data (Romer, 1994). A panel data regression approach is employed, incorporating Chow, Hausman, and Lagrange Multiplier tests. Data were obtained from the Central Statistics Agency. The findings show that both human capital and technology have a positive and statistically significant influence on economic growth. Meanwhile, government consumption contributes positively but not significantly. The study concludes that enhancing the quality of human resources and advancing technological capabilities are key drivers of regional economic growth. Keywords: Human capital, technology, government spending, economic growth, panel data